Influence of soy lecithin and sodium caseinate on the stability and in vitro bioaccessibility of lycopene nanodispersion - Yussof, Nor Shariffa; Tan, Chin Ping; Tan, Tai Boon; Utra, Uthumporn; Ramli, Muhammad Ezzudin (University of Zagreb, Faculty of Food Technology and Biotechnology, Croatia, 2023)
Research background: Various approaches have been used to present functional lipids including lycopene in a palatable food form to consumers. However, being highly hydrophobic, lycopene is insoluble in aqueous systems and has a limited bioavailability in the body. Lycopene nanodispersion is expected to improve the properties of lycopene, but its stability and bioaccessibility are also affected by emulsifier type and environmental conditions such as pH, ionic strength and temperature. Experimental approach: The influence of soy lecithin, sodium caseinate and soy lecithin/sodium caseinate at 1:1 ratio on the physicochemical properties and stability of lycopene nanodispersion prepared using the emulsification-evaporation methods before and after treatment at different pH, ionic strength and temperature were investigated. The in vitro bioaccessibility of the nanodispersions was also studied.